Settling in motion: Nyasa clandestine migration through Southern Rhodesia into the Union of South Africa: 1920s-1950s - Anusa Daimon (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Illegal African migration into South Africa is not uniquely a post-apartheid phenomenon. It has its antecedents in the colonial/apartheid period. The South Africa colonial economy relied heavily on cheap African labour from both within and outside the Union. Most foreign migrant labourers came from the then Nyasaland (Malawi) and Portuguese East Africa (Mozambique) through official channels of the Witwatersrand Native Labour Association (WNLA). WNLA was active throughout Southern Africa and competed for the same labour resources with other regional supranational "native" labour recruitment agencies, providing various incentives to lure and transport potential employees to its bustling South African gold and diamond mining industry. However, not all migrant labourers found their way through formal WNLA channels. Using archival material from repositories in Harare (Zimbabwe), Zomba (Malawi), Grahamstown (South Africa), London, and Oxford (UK), the paper casts light on illicit migration mainly by Malawian labourers (Nyasas) through Southern Rhodesia into South Africa between the 1920s and 1950s. It argues that many transient Nyasas subverted the inhibitive WNLA contractual obligations by clandestinely migrating independently into the Union. They also exploited the labour recruitment infrastructure used by the state and labour bureaus to swiftly move across Southern Rhodesia. In essence, Nyasas settled in motion, using Southern Rhodesia as a stepping-stone or springboard en-route to the more lucrative Union of South Africa. An appreciation of such informal migration opens up space for creating a more comprehensive historiography of labour migration in Southern Africa. Likewise, illicit migration is not confined to the contemporary African diaspora, but early diasporas as well. Consequently, this narrative acts as a background for understanding the precursors of the rampant illegal African migration into post-apartheid South Africa.
Keywords: 330; informal; migration; colonial; archival; Rhodesia; South Africa